Factors Influencing in Clinical Decision Making of Nurse: A Systematic Review - Baitus Sholehah; Asti Melani Astari; Rinik Eko Kapti (GoAcademica Research & Publishing, 2020)
Clinical decision making is important for nurses to do. Clinical decision making is a complex process consisting of careful assessment of pathological conditions and patient history and the use of nursing knowledge and learning based on critical thinking experiences. Improper clinical decision making will have fatal consequences for patients This review system was compiled using Proquest. Science Direct and Pubmed databases. Article selection is carried out to identify relevant articles then screening is conducted to adjust the inclusion criteria. 13 articles were obtained in accordance with inclusion criteria and reviewed by using JBI (Joanna Briggs Institute Levels). Data shows that nurses have a very important role in clinical decision making. Nurses' clinical decision making is considered due to the risks faced by patients, thus the nurses should think critically. Clinical decision making for nurses is influenced by several factors including experience, knowledge, environment, team, supervisor support, and professionalism.